Data subject rights as a research methodology: A systematic literature review - Habu, Adamu Adamu; Henderson, Tristan (Journal of responsible technology, 2023)
•Data subject rights are an increasingly popular methodological tool for collecting research data.•We gathered and analysed 32 studies that used data subject rights for data collection.•Of the various data subject rights, we find that most researchers use the right of access.•We find that most research studies using data subject rights aim at measuring legal compliance.•We outline some challenges and possible solutions for using data subject rights that can help researchers and system designers. Data subject rights provide data controllers with obligations that can help with transparency, giving data subjects some control over their personal data. To date, a growing number of researchers have used these data subject rights as a methodology for data collection in research studies. No one, however, has gathered and analysed different academic research studies that use data subject rights as a methodology for data collection. To this end, we conducted a systematic literature review that searched, compiled, and analysed 32 academic studies that use data subject rights as a data collection method. We find that the right of access is the most commonly-used data subject right by researchers, most studies are interested in measuring data subject rights compliance, and that a variety of difficulties exist in conducting research studies with data subject rights. We conclude that researchers should explore other data subject rights for alternative purposes, ease the process of exercising data subject rights, and improve the scalability of these studies.